Recentralización por otros medios: la creación de las “superdelegaciones” en el gobierno de AMLO - Olmeda, Juan Cruz (El Colegio de México A.C., 2025)
During the administration of Andrés Manuel López Obrador (AMLO) from 2018 to 2024, the federal government continued and deepened recentralization policies already present under previous administrations. To achieve this, it pursued both explicit legal reforms and more subtle changes that, while not formally altering the distribution of responsibilities between federal and subnational levels, redefined the intergovernmental balance of power in favor of the center. This article focuses on one of the most emblematic measures of the administration: the creation of the Delegations for Development Programs and the officials in charge of them, commonly known as “superdelegados” (superdelegates). It argues that, although this reform was justified in administrative terms, its primary aim was to expand the federal government’s territorial presence in the states and increase its influence over local dynamics. This was particularly relevant in the early years of AMLO’s administration, when Morena controlled only a limited number of governorships. The article examines this reform within the framework of recent literature on recentralization. Drawing on an original database, it analyzes the profile of the superdelegates and presents three key findings: the high turnover in some states, their predominantly political rather than technical background and close ties to Morena, and the significant proportion of superdelegates who left their positions to seek electoral candidacies.